Evaluating the performance of W-beam guardrail roadside safety barrier systems / Mehrtash Soltani - Mehrtash , Soltani (2016)
The last decade has witnessed an increase in the number and speed of vehicles on the roads; these situations greatly affect the occurrence of run-off crashes. Roadside safety barriers serve the purpose of redirecting errant vehicles in addition to providing high levels of safety during and after impacts. In this study, common guardrail systems, including strong-post systems, guardrails with kerbs, weak-post systems, Midwest systems and Thrie-beam rail systems are evaluated. The goal of this study is to examine the structural adequacy, the vehicle trajectory and the occupant risk factors. The implementation of a new standard Manual for Assessing Safety Hardware (MASH) for evaluating roadside safety hardware was issued in 2009. The important changes in this new standard are presented. It is found that several types of guardrail systems, including the G4(2W) guardrail system, are unable to satisfy the requirements of the MASH criteria. Therefore, in this study, several options are considered; they include improving the splice connections and adjusting the guardrail height and the post spacing to improve the performance of this system. In experimental and simulated static tests, the basic mechanical behaviour and the different stages of the deformation mechanism of the beams in a W-beam guardrail system are demonstrated. Based on the results of the static tests, the optimum mesh size for modelling a W-beam is identified for use in a full-scale model of the guardrail. The G4(2W) guardrail system is modelled in LS-DYNA and validated with a previous full-scale crash test conducted at the Texas A&M Transportation Institute. A parametric study based on the results of the LS-DYNA simulation is conducted to investigate key factors of guardrail systems, including the splice configuration, the post spacing and the guardrail height, to examine the hypotheses and to achieve the objectives of this study. The purpose of this is to find a model that satisfies the requirements of the MASH‟s criteria. Finally, a statistical analysis of the different systems highlights the effects of the main parameters, including the guardrail height and the post spacing, on the structural adequacy and the occupant risk factors. The objective is to examine the significance of each factor on the system‟s behaviour.